Adaptações fisiológicas precoces e tardias após valvotomia mitral por cateter balão - Oliveira Filho, Japy Angelini [UNIFESP] (1998)
PURPOSE: To evaluate the early and late cardiorespiratory responses after balloon mitral valvuloplasty. METHODS: Nine female patients aged 35±9 years, with mitral stenosis, in class II or III (NYHA) underwent upright ergoespirometric test, resting electrocardiogram and echocardiogram before, 3 to 5 days (early evaluation) and 8 to 12 months (late evaluation) after mitral valvuloplasty. All patients were treated with digitalis and diuretics. RESULTS: During late evaluation, 44% patients were in class II and 56% were in class I (NYHA). The resting heart rate decreased (87±11bpm vs 85±7bpm vs 75±9bpm) and the number of steps increased (4±1 steps vs 5±2 steps vs 6±1 steps); the peak oxygen uptake improved only in the late evaluation (16±3mL/kg/min vs 18±4mL/kg/min vs 22±7mL/kg/min). The anaerobic threshold, minute ventilation (VE) and ventilatory equivalent for oxygen showed no change. The heart rate (1st step: 124±18bpm vs 112±13bpm vs 87±15bpm), O2 uptake (1st step: 10±2mL/kg/min vs 8±2mL/kg/min vs 8±2mL/kg/min) and VE decreased during submaximal exercise in early and late phases. The mitral valve area decreased in the late evaluation (0.94cm² vs 1.66cm² vs 1.20cm²). CONCLUSION: Although partial restenosis tended to occur in these patients, they improved the functional class and cardiorespiratory performance and cardiocirculatory load during submaximal exercise.